HPLC fractionation with immunoassay of steroids from nipple aspirate fluid - Richard E. Heinz; Robert T. Chatterton (MethodsX, 2022)
Fractionation of steroids allows for multiple assays to be run on a single low volume liquid biopsy, whereas performing the same number of assays without fractionation would require increasing the sample volume by dilution, rendering the concentration of steroids below the level of detection for most, if not all, downstream assays. Briefly, steroids are extracted from a biofluid sample using solvent phase extraction to separate the aqueous (conjugated) steroids from the non-aqueous (non-conjugated) steroids in the organic phase. The latter is further separated by high-performance liquid chromatography (HPLC) and collected in an automated fraction collector based on the UV detection of internal standards. Commercially available immunoassays are then used to quantify the < ng/ml concentrations of steroids in each fraction. This protocol was designed for small samples of nipple aspirate fluid (minimum 2 µL), but it can be modified to fractionate steroids from homogenized solid tissue samples or other liquid biopsies. Included in this protocol are precautions to help ensure reproducibility and minimize matrix effects and other errors of measurement, given that samples requiring fractionation are fundamentally precious and, like other quantitative procedures of small samples, can be prone to contamination by solvent residues and other factors. • The method permits quantitative analysis of multiple steroids from very small volumes of biofluid. • Fractionation by HPLC provides a highly purified sample for quantification. • The immunoassay end point provides specificity without expensive equipment.